Impact of Lifestyle and Dietary Habits on Hypovitaminosis D in Type 1 Diabetes Mellitus and Healthy Children from Qatar, a Sun-Rich Country - Bener, Abdulbari; Alsaied, Amer; Al-Ali, Mariam; Hassan, Abdelmonem S.; Basha, Basma; Al-Kubaisi, Aisha; Abraham, Amit; Mian, Marcellina; Guiter, Gerardo; Tewfik, Ihab (Annals of nutrition and metabolism, 2008)
There are no population-based studies that have examined the association between vitamin D and type 1 diabetes mellitus (T1DM) and the role of lifestyle habits and dietary factors in young children in the Arabian Gulf and Middle East region. Little data on the intake of these nutrients in Mediterranean countries exist, and predictors of their suboptimal intake are not well defined. The objective of this study was to determine the association between vitamin D status and T1DM and assess the impact of lifestyle and dietary habits on hypovitaminosis D in the young population of the State of Qatar. A matched case-control study was carried out among T1DM children and healthy subjects <16 years of age at the pediatric endocrinology outpatient clinics of the Hamad General Hospital and the primary health care clinics center. The survey was conducted over a period from 6 August to 25 December 2007. The sample included 170 cases and 170 controls matched by age, gender and ethnicity. Face to face interviews were based on a questionnaire that included variables such as sociodemographic information, assessment of non-dietary covariates, assessment of dietary intake including vitamin D, type of feeding, clinical manifestations and laboratory investigations. Their health status was assessed by medical conditions, family history, body mass index, past or present clinical manifestations, serum 25(OH) vitamin D, calcium, alkaline phosphates, phosphorus, hemoglobin A1C, parathyroid hormone, magnesium and creatinine analysis. The study revealed that the incidence of severe vitamin D deficiency was considerably higher in T1DM (28.8%) compared with healthy children (17.1%). Although the mean serum level of vitamin D was significantly lower in T1DM children (15.80+/-9.23 ng/ml), compared with nondiabetic children (18.45+/-9.56 ng/ml), both groups belonged to the mild-moderate vitamin D deficiency category. A family history of vitamin D deficiency (35.3%; p=0.012) and diabetes mellitus (56.5%; p<0.001) was significantly higher in diabetic children. More than half of the diabetic (67.1%) and healthy children (51.2%) had no physical activity in their daily life. Both groups (65.9 vs. 62.9%) had very limited exposure to sunlight. Vitamin D supplement intake was very poor in diabetic children compared with healthy children; 60% of diabetic and 40.6% of healthy children never had any vitamin D supplement. The study revealed that vitamin D serum concentration, phosphorus, hemoglobin A1C, magnesium and creatinine show statistically significant differences between T1DM and healthy control subjects. A significant difference was noted between diabetic and healthy children for fractures (p=0.005), weakness (p=0.001) and gastroenteritis (p=0.025). The present study revealed that vitamin D deficiency is a common problem in Qatari children, but the incidence of vitamin D deficiency becomes very severe in T1DM children, compared with healthy children. This suggests that there is an association between vitamin D deficiency and T1DM. The data show that vitamin D status is dependent on sunshine exposure and dietary vitamin D intake. The results suggest the necessity of nutrition education to promote healthy eating habits among adolescents and their parents.